Rates and Correlates of Intimate Partner Abuse Among Indigenous Women Caregivers - Edwards, Katie M. (Journal of interpersonal violence, 2024)
Intimate partner abuse (IPA) is a public health crisis that disproportionately impacts indigenous women. We know little about rates and correlates of IPA victimization (IPAV) and abuse directed at one’s partner (ADP) among indigenous women caregivers (people who take care of children). The purpose of the current study was to address this critical gap in the literature. Participants were 44 indigenous women caregivers in the United States in a current relationship who completed a survey. Most women reported IPAV and ADP experiences in the past 6 months, and IPAV and ADP abuse directed at partner were positively associated. Further, IPAV was positively associated with adverse childhood experiences (ACEs), participants’ engagement in harsh parenting, and depressive symptoms. IPAV was negatively associated with age, income, indigenous cultural identity, and social support. ADP was positively associated with ACEs, harsh parenting, and depressive symptoms. ADP was negatively associated with age and income. ADP was not associated with indigenous cultural identity and social support. These data suggest the urgency with which efforts are needed to prevent and respond to IPA among indigenous women caregivers, especially those who are younger and of lower income, and that culturally grounded initiatives that seek to build social support may be especially impactful.